Distance Education: Parents' Perception - M. A. Abramova; R. V. Kamenev (Дискурс, 2023)
Introduction.  The  relevance  of  the study  is  due  to  the  lack  of  information  for  analyzing parents' perception of the problems of introducing distance learning in secondary schools in the conditions of COVID-19. The purpose of the study is to compare the specifics of parents' perception of opportunities and problems of distance learning in conditions of self– isolation by parents in different regions of Russia, as well as to identify attitudes that determine the prospects for its further implementation.Methodology and sources. The theoretical base is represented by the works of Russian authors  about  the  family  (A.I. Antonov, O.M. Zdravomyslova,  G.G.  Filippova).  A  review  of foreign studies of parenthood focuses on its socializing function (R. Benedict, A. Cardiner, M.  Spiro).  A  separate  block  of  works  is  devoted  to  the  problems  of  the  introduction  of  distance  education  (Gül  Özüdoğru;  Lee;  Zhao  et  al;  Garrote  et  al,  Bezrukikh  et  al,  R.S. Zvyagintsev, Yu.D. Kershi, M.A. Pinskoy). The study is based on systematic and activity-based approaches that consider parents as one of the most important factors in improving the effectiveness of distance learning. The article presents the results of an on-line survey of parents (N = 1526) in four regions of Russia (Leningrad and Irkutsk regions, Stavropol and the Republic of Bashkortostan). Data processing was carried out using the SPSS program.Results  and  discussion.  The opinion on the implementation of distance learning was studied not only regarding the education of children, but also the possibilities of using technology by parents. The study showed that they quite objectively assess the problems of implementing  distance  learning.  Parents  are  not  inclined  to  criticize  the  school,  but  they doubt the prospects of implementing the technology in the format it was introduced, arguing that it costs a lot for health, unavailability of technical equipment and the level of training of both students and schools. In relation to their training using distance learning technologies, the statements were positive.Conclusion.  A comparison of parents' responses by region showed, on the one hand, a commonality of opinions, and on the other, a significant impact on the results of the assessment of socio–cultural specifics associated with the dominant type of management, the demand for digital skills in the regional labor market.